Pelatihan Dan Pendampingan Penyusunan Laporan Keuangan Sederhana di Kantin Jone Dan Keripik Tempe Sagu Mrisi - Widyastuti, Riska Nur; Utomo, Rochmad Bayu (MAYARA: Jurnal Pengabdian Masyarakat, 2024)
This training and mentoring was carried out in Bantul Regency in two locations, namely: Sabdodadi and Mrisi for two micro enterprise groups (MSMEs) consisting of Jone canteen, and Sago Tempe Chips. This program was carried out to increase knowledge in preparing financial reports for MSMEs who have difficulty knowing their profits and losses. So there is a need for training and assistance for MSME activists in recording financial transactions and income. The methods used include interviews, which were carried out before conducting PKL where MSME activists showed that MSME activists did not have simple financial reports, as a guide for determining profit and loss. The next method is training carried out for MSME activists which includes how to record finances. method of assisting MSME activists in carrying out the preparation of financial reports. After carrying out this training and mentoring for MSME activists, they better understand the importance of financial recording, so that they can see the magnitude of profits and losses obtained while carrying out these MSME activities.